Video assisted thoracoscopic thymectomy for myasthenia gravis - Ab Rashid, Islah Munjih; Ali Yaakub, Jasmi (2010)
Background: Thymectomy is safe and effective for the management of myasthenia gravis. VATS thymectomy has the advantage of thymectomy with less invasive and more cosmetic approach compared to the standard open approach. Purpose: To study retrospectively the outcome of VATS thymectomy for myasthenia gravis in our centre (Universiti Kebangsaan Malaysia).